Dampak Pembangunan Pasar Modern (Alfamart dan Indomaret) Terhadap Pasar Tradisional (Warung Serba Ada) Kota Pekanbaru - Nurmasari, Nurmasari; Al Hafis, Raden Imam; Butarbutar, Josua (Asketik : Jurnal Agama dan Perubahan Sosial, 2019)
This research is a study related to the impact of modern market growth (Alfamart and Indomaret) on traditional markets (department stores) in the city of Pekanbaru. The theories and framework used in this research are the concept of development while the research method used is qualitative approach delivered by Jhon W. Creswell. Because of it, the expected results will be more comprehensive in relation to the impact of the existence of the modern market on traditional ones (waserda). Meanwhile, the objectives of this study are 1. Consistency of the government of Pekanbaru City on the Implementation of Regulation Number 9, 2014. 2. Perception of traditional market traders on the existence of modern markets. 3. The impact of the existence of a modern retail market (Alfamart and Indomaret) on the business of traditional traders of all-round stalls (waserda). 4. Efforts made by traditional market traders (waserda) to maintain the existence of their businesses. From the results obtained in this research, it is expected to be able to provide input and advice to the community, government and private sector on the impact of the existence of modern markets on traditional ones, and to make appropriate formulations in dealing with problems that occur. So that at the end between modern markets and traditional ones can grow and develope together and complement each other in Pekanbaru City.